Ground-based assessment of JAXA mouse habitat cage unit by mouse phenotypic studies - Fukamizu, Akiyoshi; Hamada, Juri; Shiba, Dai; Mizuno, Hiroyasu; Imamura, Yuki; Okada, Risa; Murata, Kazuya; Ito, Taito; Akiyama, Nobuko; Ito, Naoki; Noguchi, Taka-aki K.; Shirakawa, Masaki; et al. (Experimental Animals, 2016)
The Japan Aerospace Exploration Agency developed the mouse Habitat Cage Unit (HCU) for installation in the Cell Biology Experiment Facility (CBEF) onboard the Japanese Experimental Module (“Kibo”) on the International Space Station. The CBEF provides “space-based controls” by generating artificial gravity in the HCU through a centrifuge, enabling a comparison of the biological consequences of microgravity and artificial gravity of 1 g on mice housed in space. Therefore, prior to the space experiment, a ground-based study to validate the habitability of the HCU is necessary to conduct space experiments using the HCU in the CBEF. Here, we investigated the ground-based effect of a 32-day housing period in the HCU breadboard model on male mice in comparison with the control cage mice. Morphology of skeletal muscle, the thymus, heart, and kidney, and the sperm function showed no critical abnormalities between the control mice and HCU mice. Slight but significant changes caused by the HCU itself were observed, including decreased body weight, increased weights of the thymus and gastrocnemius, reduced thickness of cortical bone of the femur, and several gene expressions from 11 tissues. Results suggest that the HCU provides acceptable conditions for mouse phenotypic analysis using CBEF in space, as long as its characteristic features are considered. Thus, the HCU is a feasible device for future space experiments.